Fitness status of visually impaired learners in the Philippines: A sequential explanatory analysis - Tolentino, Julius Ceazar; Gregorio, Julie D.; Dimarucut, Alberto L.; Uy, Gilda L. (Future Science / FSH-PH Publications, 2022)
The increased awareness of the value of physical activity by introducing sports and games in the Physical Education curriculum of special education (SPED) schools in the Philippines has been both a trend and a challenge in program planning, implementation, assessment, and professional background of teachers. To evaluate the benefits of learners’ participation in physical activity, this study, therefore, measured and evaluated the health-related physical fitness status of learners in an educational institution for the visually impaired in the Philippines. The health-related physical fitness levels of blind or braille user learners (N = 12) were measured utilizing the following standardized tests: body mass index (BMI); modified sit and reach and zipper tests (flexibility); vertical jump test (power); four-level sit-ups (core strength); and 3-minute step test (cardiorespiratory endurance). Overall results revealed that the participants’ health-related physical fitness levels were below normative standards for fitness. Interviews among the special education teachers of the institution also revealed that their minimal training on fitness testing and physical activity programming, including the scarcity of materials and equipment, emerged as common problems encountered by them as far as fitness is concerned. Given the proper training on the conduct and monitoring of physical fitness tests and the facilitation of physical activity-related programs, special education teachers will be able to address the children’s needs in physical activity, fitness, and leisure programs. The results of the study will serve as inputs toward the development of a comprehensive fitness and leisure program, especially in SPED schools.